Cigarette Smoking Behaviors and Beliefs in Persons Living With HIV in Nairobi, Kenya - Jonathan Shuter; Sylvia A Ojoo; Patience Oduor; Maureen Ondire; Linda Khakali; Angela O Achieng; Tina W Masai; Wendy Potts; Melanie E Bennett; Andrea H Weinberger; Emily Koech; Seth S Himelhoch (SAGE Publishing, 2021)
Introduction Persons living with HIV (PLWH) use tobacco at higher rates than the general population in both high-income countries and low- and middle-income countries. Tobacco use rates are increasing in sub-Saharan Africa, the home to most of the world's PLWH. As the reach of antiretroviral therapy (ART) expands and HIV-related morbidity and mortality wanes, tobacco use is emerging as a leading cause of disease and death in PLWH. A better understanding of tobacco use behaviors in various settings will be crucial to designing optimal tobacco control strategies. Methods In late 2019, we enrolled 50 PLWH cigarette smokers from 6 clinical sites in Nairobi, Kenya (4 HIV care clinics and 2 methadone maintenance programs) for one-on-one interviews focusing on their behaviors and beliefs related to tobacco use. Results Fifty PLWH smokers completed the interviews. The mean age was 38.5 ± 9.7 years (range 20-57 years) and 68% were male. All were currently receiving ART. They smoked a mean of 14.9 ± 12.4 cigarettes per day, and 82% reported smoking every day. Only 6% reported dual use of smokeless tobacco products. Nicotine dependence was moderate or high in 74%. More than a third (36%) reported a prior history of tuberculosis. In our sample, use of other substances was common, especially alcohol, marijuana, and methadone. On the motivation to quit scale, 90% were at least in the contemplation stage, but only 2% had ever received behavioral cessation counseling, and only 8% had ever used pharmacotherapy (exclusively nicotine replacement therapy). Participants reported significant concern about developing smoking-related illness, exposing others to secondary smoke, and the financial burden associated with their tobacco use. Measures of intrinsic and extrinsic motivation to quit, smoker and abstainer self-concept, and social support yielded encouraging results regarding the possibility of successful quitting. Conclusions Tobacco use is an important health concern in PLWH in Kenya. A more thorough understanding of their tobacco use behaviors and beliefs will provide critical information for providers, public health officials, and policy makers as they redouble their efforts to confront this urgent health challenge.